A randomized trial to assess regional left ventricular function after stent implantation in chronic total occlusion: the REVASC trial - Mashayekhi, Kambis; Behnes, Michael; Akın, Ibrahim (JACC Cardiovascular interventions, 2018)
Objectives - The aim of this study was to investigate whether percutaneous coronary intervention (PCI) of chronic total occlusions (CTOs) improves left ventricular function. - Background - The benefit of PCI in CTOs is still controversial. - Methods - Patients with CTOs who were candidates for PCI were eligible for the study and were randomized to PCI or no PCI of CTO. Relevant coexisting non-CTO lesions were treated as indicated. Patients underwent cardiac magnetic resonance imaging at baseline and at 6 months. The primary endpoint was the change in segmental wall thickening (SWT) in the CTO territory. Secondary endpoints were improvement of regional wall motion and changes in left ventricular volumes and ejection fraction. Furthermore, major adverse coronary events after 12 months were assessed. - Results - The CTO PCI group comprised 101 patients and the no CTO PCI group 104 patients. The change in SWT did not differ between the CTO PCI (4.1% [interquartile range: 14.6 to 19.3]) and no CTO PCI (6.0% [interquartile range: 8.6 to 6.0]) groups (p = 0.57). Similar results were obtained for other indexes of regional and global left ventricular function. Subgroup analysis revealed that only in patients without major non-CTO lesions (basal SYNTAX [Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery] score ≤13) CTO PCI was associated with larger improvement in SWT than no CTO PCI (p for interaction = 0.002). Driven by repeat intervention, major adverse coronary event rates at 12 months were significantly lower in the CTO PCI group (16.3% vs. 5.9%; p = 0.02). - Conclusions - No benefit was seen for CTO PCI in terms of the primary endpoint, SWT, or other indexes of left ventricular function. CTO PCI resulted in clinical benefit over no CTO PCI, as evidenced by reduced major adverse coronary event rates at 12 months.